Mining intelligence and knowledge exploration : first international conference, MIKE 2013, Tamil Nadu, India, December 18-20, 2013. Proceedings - Kathirvalavakumar, T. (Lecture Notes in Computer Science, 2013)
This book constitutes the proceedings of the First International Conference on Mining Intelligence and Knowledge Exploration, MIKE 2013, held in Tamil Nadu, India on December 2013. The 82 papers presented were carefully reviewed and selected from 334 submissions. The papers cover the topics such as feature selection, classification, clustering, image processing, network security, speech processing, machine learning, information retrieval, recommender systems, natural language processing, language, cognition and computation and other certain problems in dynamical systems.